PROBLEMS OF TRANSLATION OF LEXICAL UNITS IN ENGLISH - Jumanazarov Samandar Urinovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article describes the translation features of lexical units in the English language. The article presents theoretical ideas in this regard and proves them with examples.